2020
DOI: 10.1038/s41598-020-58354-3
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin inhibits prostate tumor growth in high-fat diet fed mice through dual actions on adipose tissue and tumor

Abstract: This study investigated the inhibitory effect of arctigenin, a novel anti-inflammatory lignan, on prostate cancer in obese conditions both in vitro and in vivo. In vitro obese models were established by coculture of mouse adipocytes 3T3-L1 with androgen-sensitive LNCaP human prostate cancer cells, or by culturing LNCaP cells in adipocytes-conditioned medium. Arctigenin significantly inhibited LNCaP proliferation, along with decreased androgen receptor (AR) and increased Nkx3.1 cellular expression. Male severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
2
18
0
2
Order By: Relevance
“…The elevated CCL2 levels in adipose tissue and blood were also observed in humans during obesity [34], and in high-fat diet-induced [35][36][37] or genetically obese rodents [103,104]. As supported by our observations, differentiated 3 T3-L1 adipocytes cultured in vitro secret high levels of CCL2, and their co-culture with LNCaP cells significantly increased the proliferation of LNCaP cells [173]. In contrast, the restriction of caloric intake delayed PCa growth in an animal study [174].…”
Section: Ccl2-ccr2 Axis In Mediating the Interplays Among Microenvirosupporting
confidence: 81%
See 1 more Smart Citation
“…The elevated CCL2 levels in adipose tissue and blood were also observed in humans during obesity [34], and in high-fat diet-induced [35][36][37] or genetically obese rodents [103,104]. As supported by our observations, differentiated 3 T3-L1 adipocytes cultured in vitro secret high levels of CCL2, and their co-culture with LNCaP cells significantly increased the proliferation of LNCaP cells [173]. In contrast, the restriction of caloric intake delayed PCa growth in an animal study [174].…”
Section: Ccl2-ccr2 Axis In Mediating the Interplays Among Microenvirosupporting
confidence: 81%
“…In addition, Lu et al reported that elevated serum CCL2 was associated with bone metastasis in a study of 39 prostate cancer patients at various stages, suggesting the possibility of using serum CCL2 as a prognostic biomarker [26]. Since elevated CCL2 in circulation is also one of the typical features of obesity [34][35][36][37][38], this supports the role of CCL2 in connection of obesity and cancer promotion. These results suggest the critical role of the CCL2-CCR2 axis in cancer progression and its potential use as therapeutic target.…”
Section: Introductionmentioning
confidence: 78%
“…Second, we explored if CRC-associated bacterial abundances differed between cancerous and non-cancerous tissue in the same patient. Finally, we evaluated if the bacterial alterations found in CRC patients correlated with systemic inflammation, as evaluated by the circulating levels of the CCL2 cytokine marker previously found increased in several cancers and in obesity [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth remembering that inflammation is one of the initiating processes of carcinogenesis, and that the chemokines that guide the immune cells to the tumor site have been associated with increased tumor growth and progression [ 10 ]. Among cytokines, chemokine (C-C motif) ligand 2 (CCL2), also named monocyte chemoattractant protein 1 (MCP1), is produced by tumor cells and by various other cells in the host microenvironment, including adipocytes, and was reported upregulated in various tumors, including CRC, and in obesity [ 11 , 12 ]. This chemokine has been previously involved in tumor promotion under obese condition [ 13 ] and elevated circulating CCL2 levels have been associated with bone metastasis in prostate cancer patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They developed a defined system from myogenic satellite cells and muscle-derived 247 preadipocytes to examine soluble factors involved in their communication (Dodson, Vierck, 248 Hossner et al, 1997). A recent investigation by Hao and her team, established a 3T3-L1 cell co-culture system with human prostate cancer cells to determine the inhibition ability of arctigenin as an effective agent that can co-target obesity in obese-related prostate cancer (Hao, Diaz, del Rio Verduzco et al, 2020). According to another study, a co-cultured system of differentiated 3T3-L1 and RAW264.7 cells was used to study the mechanism of macrophageadipocytes interaction in innate and adaptive immunity (Lu, Ma, Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%